Innate immune system favors emergency monopoiesis at the expense of DC-differentiation to control systemic bacterial infection in mice - Pasquevich, Karina A.; Bieber, Kristin; Guenter, Manina; Grauer, Matthias; Poetz, Oliver; Schleicher, Ulrike; Biedermann, Tilo; Beer-Hammer, Sandra; Buehring, Hans-Joerg; Rammensee, Hans-Georg; Zender, Lars; Autenrieth, Ingo B.; et al. (European Journal of Immunology, 2015)
DCs are professional APCs playing a crucial role in the initiation of T-cell responses to combat infection. However, systemic bacterial infection with various pathogens leads to DC-depletion in humans and mice. The mechanisms of pathogen-induced DC-depletion remain poorly understood. Previously, we showed that mice infected with Yersinia enterocolitica (Ye) had impaired de novo DC-development, one reason for DC-depletion. Here, we extend these studies to gain insight into the molecular mechanisms of DC-depletion and the impact of different bacteria on DC-development. We show that the number of bone marrow (BM) hematopoietic progenitors committed to the DC lineage is reduced following systemic infection with different Gram-positive and Gram-negative bacteria. This is associated with a TLR4- and IFN-?-signaling dependent increase of committed monocyte progenitors in the BM and mature monocytes in the spleen upon Ye-infection. Adoptive transfer experiments revealed that infection-induced monopoiesis occurs at the expense of DC-development. Our data provide evidence for a general response of hematopoietic progenitors upon systemic bacterial infections to enhance monocyte production, thereby increasing the availability of innate immune cells for pathogen control, whereas impaired DC-development leads to DC-depletion, possibly driving transient immunosuppression in bacterial sepsis.
EVALuna2:7688